Criminal advocacy: a student's guide - Ab Hamid, Zuraini (Harun M.Hashim Law Centre, 2022)
This book was specifically written for law students and newly admitted attorneys looking for practical guidelines on handling criminal matters and courtroom trials at the start of their legal careers. This book aims to guide handling criminal court cases from the outset to the conclusion. It was written in a simple manner and style to enable the reader to understand the content, examples and exercises.